Molecular imaging in the aid of drug delivery technology - Cho, Yong Woo; Kim, Kwangmyeung; Park, Kinam; Kwon, Ick Chan (Macromolecular research, 2014)
Molecular imaging aims to visualize biological processes in a living system at a molecular or cellular level while drug delivery systems (DDS) aim to deliver drugs to specific targets of tissues or organs at a controlled rate. Molecular imaging and DDS, seemingly two different subjects, however, are not completely separate. They share overlapped conceptual and technological spectra. To visualize molecular events in body molecular imaging requires delivery of imaging probes to specific targets, which has been the main technology developed in DDS for decades. Simply replacing drugs in targeted therapeutic DDS with imaging probes turns the whole system to targeted imaging system for diagnosis of diseases. Integrating imaging probes into therapeutic DDS is a starting point for theragnotics, therapy, and diagnosis performed simultaneously with one agent. Key DDS technologies applied to molecular imaging have played an important role in advances of molecular imaging. We here briefly discuss molecular imaging in the aid of drug delivery technology, with an emphasis on theragnotics of tumors.